2020
DOI: 10.1038/s41467-020-15661-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of contemporaneous peer punishment on cooperation with the future

Abstract: We use a laboratory version of the intergenerational goods game (IGG) to investigate whether peer punishment facilitates the successful provision of multigenerational public goods. In our experiment, groups (generations) decide sequentially about the provision of a multigenerational public good through the voluntary contributions of their members. Successful provision requires that contributions meet a threshold and exclusively benefits members of future generations. Provision costs are borne only by the curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 49 publications
(73 reference statements)
1
15
0
1
Order By: Relevance
“…We contribute to the increasing literature on behavioral dynamics in intra-and intergenerational climate change dilemmas [54][55][56]. In line with previous research on intra-generational conflicts of climate change mitigation [10], our results indicate that individuals are willing to contribute in order to avoid the substantial risks associated with climate change.…”
Section: Discussionsupporting
confidence: 87%
“…We contribute to the increasing literature on behavioral dynamics in intra-and intergenerational climate change dilemmas [54][55][56]. In line with previous research on intra-generational conflicts of climate change mitigation [10], our results indicate that individuals are willing to contribute in order to avoid the substantial risks associated with climate change.…”
Section: Discussionsupporting
confidence: 87%
“…To build sustainable societies, intergenerational sustainability dilemmas must be resolved; the present generation must act altruistically toward future generations-that is, restrict contemporary gains and instead emphasize the benefit of future generations. In accordance with the rising importance of this issue, the number of studies regarding decisions relating to intergenerational sustainability dilemmas has recently increased (e.g., [2][3][4][5][6] ). This study aims to detect and identify the type of altruistic preference for future generations related to intergenerational dilemmas.…”
Section: People Prefer Joint Outcome Prosocial Resource Distribution mentioning
confidence: 99%
“…Although some studies that feature economic games indicate that most people do not choose the sustainable option in normal conditions, people have been found to behave altruistically toward subsequent generations when appropriate conditions are applied 11 . Moreover, studies that feature public goods games with intergenerational structures report that the majority of participants left sufficient resources for the next generation 3,6 . These studies demonstrate that people may have altruistic preferences for future generations.…”
Section: People Prefer Joint Outcome Prosocial Resource Distribution mentioning
confidence: 99%
“…A new experimental paradigm, intergenerational common-pool resource (ICPR) games, has been proposed for studying intergenerational cooperation [ 5 , 30 , 31 ] and may provide insights into how to enhance it. ICPR experiments have previously found that the resource typically deteriorates over generations unless an additional mechanism is added, such as voting or punishment [ 30 , 31 ]. However, these experiments have simulated generations as sequential groups of strangers and assumed the future outcomes do not influence the current generation (i.e.…”
Section: Introductionmentioning
confidence: 99%